The Antioxidant Compounds Contained in n-Butanol and Aquamor Fractions of Dischidia Nummumaria Extract - Abner A. Leba; Sherly M. F. Ledoh; Yohanes Buang (Journal of Applied Chemical Science, 2012)
There have been elucidated the antioxidant compounds contained in n-butanol and aquamor fractions of methanol extracts isolated from dischidia nummularia. The study was firstly started by maceration of dischidia nummularia powder in certain quantity of pure methanol solvent and followed by gradual partition with n-butanol and aquamor water and then purified with column chromatography. The chemical contents migrated into both those later solvents were detected by LC-MS and their functional groups were detected by FT-IR instruments. The results showed that methanol extract and those n-butanol and aquamor fractions contained 24, 14, and 15 compounds, respectively. The compounds contained in those three samples involve myricetin, quercetin, kaempferol, quercetin-3-ogalactoside, quercetin-3-orhamnoside, quercetin-3-oglucoside, kaemp-ferol galactoside, kaempferol-3- oglucoside, luteolin, and catechin. These compounds have been reported to have behaviors as antioxidant as reviewed in various literatures (see result and discusion). Furthermore, the FT-IR spectrum provides information regarding the functional group and element group of those antioxidant compounds. Based on those reports therefore the methanol extract and the n-butanol and aquamor fractions of dischidia nummularia isolated have those antioxidant compounds.